If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 6n = 15 Solving m + 6n = 15 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6n' to each side of the equation. m + 6n + -6n = 15 + -6n Combine like terms: 6n + -6n = 0 m + 0 = 15 + -6n m = 15 + -6n Simplifying m = 15 + -6n
| 18x-2x+x=102 | | 10-2b=4b-8 | | 2=2v+8 | | ax^2-ax=0 | | 28-20x=2x+25-16x-12-6x | | a-3=-14 | | y/7+6=-15 | | 5y+1=3y+18 | | -6=2(x) | | 4-12x=100 | | 15(x)=-75 | | 4m-3(m+5)=-(3m-5) | | 5-6a+7+2a=8a-2-15a+5 | | -5x+7=4 | | 2k-10= | | 120-7x=20x+18 | | 13x-218=6x-8 | | -16-4=9 | | 11x-238=3x-14 | | x(5x-4)(x+7)= | | 24.5/5-4= | | X+1-2=45 | | 2k-10=8 | | x^2+36=-18 | | .12(2s)+.12+s=4 | | 2222*2222= | | 159-10x=8x+21 | | 5(7n-19)=19n-5 | | 2x^2-15x-18=0 | | 2X^2+4x-26=0 | | -24-9=7x+24 | | (5x+2)(3y-8)= |